A prediction model for early systemic recurrence in breast cancer using a molecular diagnostic analysis of sentinel lymph nodes: A large‐scale, multicenter cohort study. Issue 10 (28th February 2022) - Osako, Tomo; Matsuura, Masaaki; Yotsumoto, Daisuke; Takayama, Shin; Kaneko, Koji; Takahashi, Mina; Shimazu, Kenzo; Yoshidome, Katsuhide; Kuraoka, Kazuya; Itakura, Masayuki; Tani, Mayumi; Ishikawa, Takashi; et al.
Abstract : Background: The one‐step nucleic acid amplification (OSNA) assay can quantify the cytokeratin 19 messenger RNA copy number as a proxy for sentinel lymph node (SN) metastasis in breast cancer. A large‐scale, multicenter cohort study was performed to determine the prognostic value of the SN tumor burden based on a molecular readout and to establish a model for the prediction of early systemic recurrence in patients using the OSNA assay. Methods: SN biopsies from 4757 patients with breast cancer were analyzed with the OSNA assay. The patients were randomly assigned to the training or validation cohort at a ratio of 2:1. On the basis of the training cohort, the threshold SN tumor burden value for stratifying distant recurrence was determined with Youden's index; predictors of distant recurrence were investigated via multivariable analyses. Based on the selected predictors, a model for estimating 5‐year distant recurrence–free survival was constructed, and predictive performance was measured with the validation cohort. Results: The prognostic cutoff value for the SN tumor burden was 1100 copies/μL. The following variables were significantly associated with distant recurrence and were used to construct the prediction model: SN tumor burden, age, pT classification, grade, progesterone receptor, adjuvant cytotoxic chemotherapy, and adjuvant anti–human epidermal growth factor receptor 2 therapy. The values for the area under the curve, sensitivity, specificity, and accuracy of the prediction model were 0.83, 63.4%, 81.7%, and 81.1%, respectively. Conclusions: Using the OSNA assay, the molecular readout–based SN tumor burden is an independent prognostic factor for early breast cancer. This model accurately predicts early systemic recurrence and may facilitate decision‐making related to treatment. Abstract : The molecular‐based tumor burden in sentinel lymph nodes is an independent prognostic factor for early breast cancer. This model can accurately predict early systemic recurrence, and the one‐step nucleic acid amplification assay may guide therapeutic decision‐making for patients.